(untitled) (Journal of Applied and Natural Science, 2018)
A smart and modern technique based upon information and communication technology (ICT) was conceptualized and developed. It facilitates pests’ information collection timely, its fast processing and planning with quickly implementable options - to manage biotic stresses on field crops on large-scale area basis. The pest mapping in field crops (paddy, cotton) in different agro-ecosystems of India was done based on using Geographic Information System (GIS) Arc-info package. To fast track the decision-making, its mass communication to farming community, an exhaustive e-database of plant protection measures as recommended by different agencies in the country for different field crops viz., cereal crops, oilseed crops, pulses, fibre crops, sugar crops, fodder crops etc. - had also been prepared and digitized. The outcome and benefits of this technique had been analyzed and findings - that demonstrate the benefits of using the proposed architecture are also detailed.